If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + 3) + 6x + 1 = 43 Reorder the terms: 3(3 + 4x) + 6x + 1 = 43 (3 * 3 + 4x * 3) + 6x + 1 = 43 (9 + 12x) + 6x + 1 = 43 Reorder the terms: 9 + 1 + 12x + 6x = 43 Combine like terms: 9 + 1 = 10 10 + 12x + 6x = 43 Combine like terms: 12x + 6x = 18x 10 + 18x = 43 Solving 10 + 18x = 43 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 18x = 43 + -10 Combine like terms: 10 + -10 = 0 0 + 18x = 43 + -10 18x = 43 + -10 Combine like terms: 43 + -10 = 33 18x = 33 Divide each side by '18'. x = 1.833333333 Simplifying x = 1.833333333
| 4x+36x=93 | | 3+21=15 | | 3+21=21 | | 0.625(a-2)= | | m+3(m-4)=20 | | 4(5-x)=-(1+x) | | 2+4(x+6)=4(2x+3)+6 | | 7(4+n)=4n+37 | | 2(m+5)=16 | | 54+2x=180 | | 4(2x+3)=11x+6 | | 20=5y+5 | | 180=2x-18 | | 525.00+0.21x=600 | | 2t+7=t+9 | | 76-x=3x | | 7n+2=5n+20 | | 9x+4=8x+7 | | 4t^2+48t=160 | | -2v^2-1v+12=-3v^2+6v | | 2x+4y+.25z=100 | | (-8/5)x-6=-54 | | 4m+4=4(m+1) | | 6x-4+4x-6=180 | | 2x+46+x-18+x=180 | | y^2+2xy-3x^2=0 | | 525.00+0.21x=850.00+0.31x | | 2x+46+x-18=180 | | 525.00+0.21x=850.00+0.31 | | 6x-4+7x-4+5x+8=180 | | 12+6q(5-q)= | | -(1+6k)+4k=-8k-7(k+2) |